2007
DOI: 10.1086/519739
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Expression of mRNA of Interferon‐γ, Tumor Necrosis Factor–α, Interleukin‐10, Nitric Oxide Synthase, Indoleamine‐2,3‐Dioxygenase, and RANTES Is a Major Immune Effector in Mediterranean Spotted Fever Rickettsiosis

Abstract: Mild/moderate MSF is associated with a strong and balanced intralesional proinflammatory and anti-inflammatory response, with a dominant type 1 immunity, whereas severe MSF is associated with increased expression of chemokine mRNA. Whether these factors are simply correlates of mild and severe MSF or contribute to antirickettsial immunity and pathogenesis remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
3
27
0
1
Order By: Relevance
“…In addition, increased production of several chemokines including RANTES and MCP-1 that are potent NK cell and T cell chemoattractants 36,37 suggest that enhanced trafficking of NK cells to the liver may contribute to severe tissue injury and host cell death in lethal disease. This conclusion is consistent with previous studies showing higher levels of RANTES in patients with fatal Mediterranean spotted fever rickettsiosis compared with patients with mild disease, 38 as well as higher serum levels of CCL2 (MCP-1) in fatal murine primary and secondary ehrlichiosis compared with mild ehrlichiosis where blocking CCL2 ameliorates fatal disease. 39 In an influenza model where severe disease is due to T cell-mediated injury, it has been suggested that TNF-␣ regulates the production of MCP-1 and possibly other chemokines by host cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, increased production of several chemokines including RANTES and MCP-1 that are potent NK cell and T cell chemoattractants 36,37 suggest that enhanced trafficking of NK cells to the liver may contribute to severe tissue injury and host cell death in lethal disease. This conclusion is consistent with previous studies showing higher levels of RANTES in patients with fatal Mediterranean spotted fever rickettsiosis compared with patients with mild disease, 38 as well as higher serum levels of CCL2 (MCP-1) in fatal murine primary and secondary ehrlichiosis compared with mild ehrlichiosis where blocking CCL2 ameliorates fatal disease. 39 In an influenza model where severe disease is due to T cell-mediated injury, it has been suggested that TNF-␣ regulates the production of MCP-1 and possibly other chemokines by host cells.…”
Section: Discussionsupporting
confidence: 93%
“…19 Moreover, de Sousa et al have recently showed that the intralesional mRNA expression of the CC-chemokine Regulated on activation, normal T cell expressed and secreted (RANTES) was significantly higher in patients with severe as compared to those with mild MSF. 21 In the present study we screened for the expression of eight different CC-and CXC-chemokines, and demonstrated that both R. africae and R. conorii selectively induced IL-8 and MCP-1 in HUVEC in a dose-dependent manner as shown both at the mRNA and protein levels. However, while the MCP-1 response showed no difference between R. africae and R. conorii, the IL-8 response was markedly enhanced in R. conorii-activated endothelial cells, but not in R. conorii-activated PBMC, as compared with R. africae-activated cells.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, de Sousa et al (14) have recently reported that the intralesional cytokine expression profile is characterized by a mixed, proinflammatory and anti-inflammatory response, as reflected by elevated levels of mRNA expression of IFN-␥, TNF-␣, and IL-10, in patients with MSF. Higher intralesional expression of IFN-␥ mRNA correlates with mild/ moderate MSF, suggesting that there is an IFN-␥-mediated reduction in bacterial load in these patients and that the simultaneous expression of higher levels of immunosuppressive IL-10 mRNA may decrease responsiveness to IFN-␥ (36).…”
Section: Discussionmentioning
confidence: 99%